Demystifying “absolute truths” of additive manufacturing - Oliveira, J. P. (2024)
Authors received funding from the European Institute of Innovation and Technology (EIT) \u2013 Project Smart WAAM: Microstructural Engineering and Integrated Non-Destructive Testing. This body of the European Union receives support from the European Union's Horizon 2020 research and innovation programme. Publisher Copyright: © 2024 The Authors